2004
DOI: 10.1021/la0356001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Mesh Structures at Solid/Solution Interfaces by Atomic Force Microscopy

Abstract: The formation of adsorbed surfactant layers consisting of a mesh or network of branched cylindrical aggregates on muscovite mica by several surfactant systems is described. The curvature of the adsorbed aggregates is varied by a variety of mechanisms that all generate morphologies between adsorbed cylinders and bilayers, and the resulting lateral structure is imaged by "soft contact" atomic force microscopy. We compare the direct images and Fourier transforms of the adsorbed layer structures, and relate them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 39 publications
(78 reference statements)
7
34
0
Order By: Relevance
“…3 shows 95 nm × 95 nm AFM deflection images of the transformation of cylindrical structure of DTAB (2 cmc) into a bilayer with increasing proportion of MEDDAB. As expected from studies of DDAB/DTAB mixed films [24], increasing the proportion of a surfactant with a spontaneous curvature favouring planar structures results in a reduction in the net curvature of the mixed film. The cylindrical morphology favoured by DTAB persists to a 21:79 MEDDAB:DTAB bulk composition.…”
Section: E 23 and Meddab Mixed Filmssupporting
confidence: 64%
See 1 more Smart Citation
“…3 shows 95 nm × 95 nm AFM deflection images of the transformation of cylindrical structure of DTAB (2 cmc) into a bilayer with increasing proportion of MEDDAB. As expected from studies of DDAB/DTAB mixed films [24], increasing the proportion of a surfactant with a spontaneous curvature favouring planar structures results in a reduction in the net curvature of the mixed film. The cylindrical morphology favoured by DTAB persists to a 21:79 MEDDAB:DTAB bulk composition.…”
Section: E 23 and Meddab Mixed Filmssupporting
confidence: 64%
“…A wealth of AFM studies of surfactant self-assembly on various substrates have revealed the existence of globular [20], cylindrical [16,17], mesh [24,25] and bilayer [17,26] structures. The effects of factors such as alkyl chain length [15], headgroup structure and charge [18,20], counterion type [20] and electrolyte concentration [27,28] all been found to mirror the structural trends observed in bulk self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a jump-in process happens following the maximum force. The long-range repulsive force is typical for the study of the adsorption of cationic surfactants at solid-solution interface and the repulsion is believed to give information on the structures of the adsorbed surfactant aggregates [14]. In the present system, the long-range repulsive force is suspected to indicate the presence of C 12 C 6 C 12 Br 2 bilayer aggregates at the solidsolution interface.…”
Section: Force-distance Curvementioning
confidence: 68%
“…Differently, for the adsorption of the traditional single-chain surfactant, the wormlike micelles or hemimicelles were always found at the solid-solution interfaces by the in situ AFM imaging [10,12,14,19]. This may be attributed to the different molecular nature of the single-chain surfactants and the gemini surfactants.…”
Section: Force-distance Curvementioning
confidence: 89%
See 1 more Smart Citation